(untitled) (Bodhi Path, 2026)
Having lost her entire family in a tragic sequence of events, Paṭācārā wandered in a state of shock and madness, stripped of all awareness and clothed in destitution. Owing to the force of her past merits, she one day passed near Jetavana Monastery, where the Blessed One was delivering a discourse to a large assembly. Seeing her approach, the crowd attempted to drive her away, fearing that this distraught woman might disturb the gathering. However, the Buddha noticed her and restrained the people. The sorrow-stricken woman came forward. With boundless compassion, the Buddha addressed her: “My poor daughter, regain your awareness.” His voice carried a healing force. Hearing these words, she gradually recovered clarity. Realizing that she was unclothed, she felt shame and crouched on the ground. Someone nearby covered her with a robe, which she immediately wrapped around herself. Having previously fallen into degraded conduct, she later became known as Paṭācārā after her ordination. References 1. थेरीगाथापालि (१२७-१३२)